Essays. - Cotsonis, John A., author.
1 online resource (1 volume
Keywords: "The articles republished in this volume are ground-breaking studies that employ a large body of religious figural imagery of Byzantine lead seals ranging from the 6th to the 15th century. A number of the studies present tables, charts and graphs in their analysis of iconographic trends and changing popularity of saintly figures over time. And since many of the seals bear inscriptions that include the names, titles or offices of their owners, information often not given for the patrons of sacred images in other media, these diminutive objects permit an investigation into the social use of sacred imagery through the various sectors of Byzantine culture: the civil, ecclesiastical and military administrations. The religious figural imagery of the lead seals, accompanied by their owners' identifying inscriptions, offers a means of investigating both the broader visual piety of the Byzantine world and the intimate realm of their owners' personal devotions. Other studies in the volume are devoted to rare or previously unknown sacred images that demonstrate the value of the iconography of Byzantine lead seals for Byzantine studies in general. This volume includes various articles focusing on sphragistic images of saints and on the religious imagery of Byzantine seals as a means of investigating the personal piety of seal owners, as well as the wider realm of the visual piety and religious devotions of Byzantine culture at all levels. A companion volume includes studies dedicated to the image of Christ, primarily found on imperial seals, various images of the Virgin, and narrative or Christological scenes"--